Comparison of Alternative Forms of Teaching Fundamentals of Accounting. - Laughlin, Eugene J.; Gentry, James W.; May, Carolyn A. (The Accounting Review, 1976)
From these results it can be inferred that self-paced instruction using audio-visual instruments is as meaningful a learning tool as the traditional lecture-discussion format. There were no significant differences between performances in the audio-visual sections and the students' performances in the traditional section. The progress of the students from the audio-visual sections in subsequent accounting courses currently is being monitored. Preliminary results, not reported here, indicate that students from these sections have performed as well in upper-level accounting courses as have students from the traditional sections. A second inference from our reported data is that the students' past performances, as measured by their GPA's, were correlated more highly to the students' performances in the audio-visual sections than they were in the traditional section. Informal discussions with individual students revealed that the better students, as measured by their GPA's, liked the freedom of getting the work done ahead of schedule, thus enabling them to concentrate on other courses. All students completing the course early were in the upper half of the overall GPA's and received grades of A or B in the course. The informal discussions also indicated that the lower GPA of the poorer students frequently was caused by a lack of motivation. Thus, the self-paced format with its stress on individual motivation may be more harmful to the poorer students than would be the traditional format.